Characteristic features of cutaneous melanoma in a dermatology referral centre in Tehran, Iran. (15th March 2017) - Kamyab, Kambiz; Kazemi, Sheyda; Azimi, Pourya; Azizpour, Arghavan; Ghandi, Narges; Pirooz, Elham; Noormohammadpour, Pedram; Mirshams‐Shahshahani, Mostafa; Daneshpazhooh, Maryam
Abstract: Background/Objectives: The characteristics of cutaneous melanoma in the Middle‐Eastern countries is poorly described. Therefore we conducted this study to determine the characteristics of melanoma in Iran. Methods: A retrospective, cross sectional study of melanoma patients seen at a tertiary referral centre, Iran, from May 2004 to October 2014. Clinical data included age and gender of the patients at the time of diagnosis, tumour location and tumour size. Histological characteristics included Breslow thickness, Clark level and subtype of tumour. Results: A total of 450 cases of melanoma with a male/female ratio of 1.1:1 were reviewed. The mean age of patients was 57.5 years. The most frequent histological subtypes were acral lentiginous melanoma (30%) and lentigo maligna melanoma (29%). In 215 cases (49%) the tumour was located on the extremities. The second most common site was the face. Tumour invasion was mainly at Clark level III and IV. The mean Breslow thickness was 2.8 mm; 143 (38%) melanomas had a Breslow thickness less than 1 mm (T1) and 86 (23%) were more than 4 mm (T4). Conclusion: This study indicates that clinical and histological features of melanoma in Iranians (who are mainly of skin phototypes 3–4) are different from those observed in Western countries. Further cohort studies are required to evaluate the role of ethnic and environmental risk factors for melanoma in different populations.